THE IMPORTANCE OF DIAGNOSTIC APPROACHES IN THE MODERN ERA - Adash Rustamova Eshankulovna; Boyqobilova Madina Umar qizi (Scholar Express Journals, 2023)
This article reveals the importance of diagnostic approaches in the modern era. Besides that, the implication of diagnostic assessment and it’s approaches, features have been discussed.
Keywords: Diagnostic approaches; assessment; strengths and weaknesses in a learner’s knowledge